OPEN EDUCATIONAL RESOURCES IN NON-ENGLISH- SPEAKING COUNTRIES - Svetlana Yu. Knyazeva (Высшее образование в России)
The article presents the results of the UNESCO Institute for Information Technologies in Education project «The Open Educational Resources (OER) in non-English speaking countries» for 2010-2014. Main objective of the project is promoting of the of open educational resources and skills development for their creation, sharing and distribution in UNESCO Member States. Based on the implemented analysis of the requirements, potential, opportunities and problems arising during OER creation and use, the IITE experts develop recommendations on extension of OER use in educational practice.